5 - The Emergence of Public Spheres in Colonial Cameroon: Palm Wine Drinking Joints in Bamenda Township - Fru, Nicodemus Awesome (Africa Development, 2021)
Habermas’ concept of public sphere encompasses a variety of meanings, including social sites where meanings are articulated, distributed and negotiated, as well as the collective body constituted by – i.e. ‘the public’ in this process. Thus, any area in social life where people congregate and freely discuss and identify societal problems and, through that discussion influence public and political action, constitutes the public sphere. This paper argues that Habermas’ conception is relevant to Africa and sets out to examine the emergence, functioning, and consequences of palm wine drinking joints in 20th century colonial Bamenda Township as public spheres par excellence à la Habermas.